Atención al cliente en la casa musical mejor sonido de Guayaquil, período 2022. - Sevillano López, Julio Santiago (2023)
This case study will be carried out in the company Casa Musical Mejor Sonido in the city of Guayaquil, with the purpose of knowing if the customer service used by the company is adequate, this investigative work allowed, through the blueprint technique, to increase fidelity and satisfaction to improve a user's experience. In addition to identifying through a survey that was carried out on the commercial clients, measuring the level of satisfaction they had with the company and knowing the factors that generate problems in the sales service that is applied in the company, techniques such as blueprint and the survey allowed the collection of sufficient information to know the point of view and perspectives of people who buy a musical instrument, observe and analyze their behavior to understand their needs, and thus be able to identify problems and improve customer service, maintain their loyalty and expand into new segments. It was possible to conclude that the attention provided by the employees when addressing customers when they made a purchase of their products was deficient, for which it was suggested that their employees should be trained to improve customer treatment, use effective tools, such as a survey and training for workers to identify internal problems that affect the quality of service and thus improve the sales of the commercial. In this case study, the importance of knowing the tastes and preferences of customers and the strategies that the company must apply to promote customer loyalty and obtain greater recognition in the market were also described.